PENGARUH KONFLIK TERHADAP KARAKTER TOKOH DALAM NOVEL BIMALA KARYA RABINDRANATH TAGORE - Devi Safitri; Christanto Syam; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated by the desire of researchers to find the influence of conflict on the character of characters in the novel Bimala by Rabindranath Tagore. Because conflict often becomes a factor that influences human psychological changes resulting in behavior and attitudes. The problems in this study included three things, namely the influence of internal conflict on character, the influence of external conflict on the character of the character, and the plan for implementation in school. The theories used in this discussion included understanding the characters, understanding novels, conflicts in literary works, psychology in literature, and literary learning in school. The method used in this study was descriptive method with qualitative research. The approach used was a psychological psychology approach. The technique used was a documentary study technique with a data collection tool that was the researcher himself as a key instrument. The data in this study are conflicts that affect the character of the character. The data analysis technique used was to re-read the data that has been classified and validated, analyze the data relating to the influence of internal and external conflicts on character figures.Keywords: Bimala novel, character of character, influence of conflict